Evaluation of Shear Bond Strength Between Denture Teeth and 3D-Printed Denture Base Resin - Cleto, Marília P. [UNESP]; Silva, Marcela D. D. [UNESP]; Nunes, Thaís S. B. S. [UNESP]; Viotto, Hamile E. C. [UNESP]; Coelho, Sabrina R. G. [UNESP]; Pero, Ana C. [UNESP] (Wiley, 2022)
Purpose: The aim of this study was to evaluate the bond strength between two types of artificial teeth with a 3D-printed denture base resin using different bonding agents. Materials and methods: Two types of artificial teeth were evaluated: 3D-printed (Cosmos TEMP) and prefabricated polymethylmethacrylate (Biotone) bonded to cylinders (2.5 mm in height and 5 mm in diameter) of 3D-printed denture bases (Cosmos Denture designing by Meshmixer and printed by Flashforge Hunter DLP Resin 3D Printer). Two combinations between denture base and artificial teeth were eveluated: Cosmos Denture – Biotone, n = 30, and Cosmos Denture - Cosmos TEMP, n = 30. For each combination, the specimens were randomly distributed according to the bonding agent: (1) autopolymerized acrylic resin-Duralay, n = 10; (2) 3D-printed resin Cosmos TEMP, n = 10; and (3) methylmethacrylate monomer (MMA) + 3D-printed resin Cosmos TEMP, n = 10, totaling 60 specimens. The application of MMA was done conditioning the tooth surface for 180 seconds; the other agents were applied on the same surface. The virtual design of the 3D-printed resin teeth was obtained by scanning the first maxillary molar of the prefabricated teeth as the same protocol of cylinders. The control group (n = 10) was a conventional heat-polymerized denture base resin (Lucitone 550) bonded to the prefabricated resin teeth (Biotone). The shear bond tests were performed by applying a perpendicular force to the artificial tooth – denture base resin, through a chisel at 1 mm/min until failure. Two-way ANOVA and Bonferroni post hoc tests (α = 0.05) were used for multiple comparisons. Results: For the Biotone tooth, the bond strength was significantly higher using MMA + Cosmos TEMP (10.04 MPa), and similar to the control (11.84 MPa, p = 0.484). For the 3D-printed tooth (Cosmos TEMP), the bond strength using the agents Cosmos TEMP (9.57 MPa) and MMA + Cosmos TEMP (12.72 MPa) were similar to the control (11.84 MPa, p = 0.169 and p = 1, respectively), but different from each other (p = 0.016). Conclusions: From the results, it is recommended to use: MMA + Cosmos TEMP bonding agent for the Biotone tooth; and Cosmos TEMP or MMA + Cosmos TEMP bonding agents for the Cosmos TEMP tooth, both attached to the 3D-printed denture resin Cosmos Denture.
Keywords: 3D-printing; acrylic resins; artificial; complete denture; denture bases; tooth